Intergenerational transmission of genetic risk for hyperactivity and inattention. Direct genetic transmission or genetic nurture? - Ivan Voronin; Isabelle Ouellet‐Morin; Amélie Petitclerc; Geneviève Morneau‐Vaillancourt; Mara Brendgen; Ginette Dione; Frank Vitaro; Michel Boivin (Wiley, 2024)
Abstract Background Hyperactivity and inattention, the symptoms of ADHD, are marked by high levels of heritability and intergenerational transmission. Two distinct pathways of genetic intergenerational transmission are distinguished: direct genetic transmission when parental genetic variants are passed to the child's genome and genetic nurture when the parental genetic background contributes to the child's outcomes through rearing environment. This study assessed genetic contributions to hyperactivity and inattention in childhood through these transmission pathways. Methods The sample included 415 families from the Quebec Newborn Twin Study. Twins' hyperactivity and inattention were assessed in early childhood by parents and in primary school by teachers. The polygenic scores for ADHD (ADHD‐PGS) and educational attainment (EA‐PGS) were computed from twins' and parents' genotypes. A model of intergenerational transmission was developed to estimate (1) the contributions of parents' and children's PGS to the twins' ADHD symptoms and (2) whether these variances were explained by genetic transmission and/or genetic nurture. Results ADHD‐PGS explained up to 1.6% of the variance of hyperactivity and inattention in early childhood and primary school. EA‐PGS predicted ADHD symptoms at both ages, explaining up to 1.6% of the variance in early childhood and up to 5.5% in primary school. Genetic transmission was the only significant transmission pathway of both PGS. The genetic nurture channeled through EA‐PGS explained up to 3.2% of the variance of inattention in primary school but this association was non‐significant. Conclusions Genetic propensities to ADHD and education predicted ADHD symptoms in childhood, especially in primary school. Its intergenerational transmission was driven primarily by genetic variants passed to the child, rather than by environmentally mediated parental genetic effects. The model developed in this study can be leveraged in future research to investigate genetic transmission and genetic nurture while accounting for parental assortative mating.